The effectiveness of using paper stick puppets to teach speaking - Elita, Yulia Jannata; Zuhriyah, Mukminatus (Journal of English Language and Pedagogy, 2022)
This research was conducted at SMP N 2 Plandaan. There were several problems that have been found. Therefore, the researcher limits the problem only to the student’s speaking ability which has three indicators: fluency, pronunciation, and vocab or content. There were three objectives, namely to determine students' speaking skills before being taught using paper stick puppets as media to teach speaking skills, students' speaking skills after being taught using paper stick puppets as media to teach speaking skills, and whether there is a significant effect of using paper stick puppets on the speaking skills at VII D class in SMP N 2 Plandaan or not. This research used a pre-experimental design. Especially used a one-group pre-test and post-test design. The researcher used a purposive sampling technique, where class VII D became the sample consisting of 26 students. The data collection techniques used were speaking tests. After collecting the data, the researcher got pre-test and post-test scores which the mean pre-test being 56.73 and the mean score post-test being 67.46. Next, the researcher found that obtained was 6.559, then the table was 2.060 at the 5% level and 2.787 at the 1% level and can be written as 2.060<6.559>2.787. So, it means that Ha was accepted and Ho was rejected. In the end, the researcher summarized that using paper stick puppets has significant effectiveness for teaching speaking skills at class VII D of SMP N 2 Plandaan Jombang.